Ignition of Mediterranean Fuel Beds by Several Types of Firebrands - Viegas, D X; Almeida, M; Raposo, J; Oliveira, R; Viegas, C X (Fire Technology, 2012)
An experimental laboratory study on the probability of ignition and ignition time delay of new ﬁres for 11 pairs of burning embers and fuel beds of species common in Mediterranean forests is presented. For the no wind conditions of the present tests it was found that positive ignition was achieved only for embers with ﬂaming combustion. Fuel bed moisture content was identiﬁed as a very important parameter to assess probability of ignition and ignition time delay. In the range of the present tests it was found that ignition depended more on fuel bed properties than on ember characteristics.
Keywords: Forest fires; fuel bed ignition; spot fires